2018
DOI: 10.1002/ejhf.1146
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with insulin is associated with worse outcome in patients with chronic heart failure and diabetes

Abstract: Whether insulin use is associated with poor outcomes in HF should be investigated further with controlled trials, as should the possibility that there may be safer alternative glucose-lowering treatments for patients with HF and type 2 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
1
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(94 citation statements)
references
References 37 publications
(39 reference statements)
7
77
1
3
Order By: Relevance
“…Previously we showed that, among patients with concurrent HFrEF and diabetes, those treated with insulin have worse symptoms, more signs of congestion and greater risks of death and HF hospitalization compared with those not on insulin . We believe our present report is the first to extend these observations to patients with HFpEF, and we have also identified additional, novel findings in this HF phenotype.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Previously we showed that, among patients with concurrent HFrEF and diabetes, those treated with insulin have worse symptoms, more signs of congestion and greater risks of death and HF hospitalization compared with those not on insulin . We believe our present report is the first to extend these observations to patients with HFpEF, and we have also identified additional, novel findings in this HF phenotype.…”
Section: Discussionsupporting
confidence: 72%
“…Theoretically, insulin may be detrimental to patients with concomitant HF, but this has yet to be tested in a randomized clinical trial in patients with established HF. In a post‐hoc analysis of the Candesartan in Heart failure: Assessment of Reduction in Mortality and morbidity (CHARM) trial, insulin therapy was associated with higher risks of mortality and HF hospitalization in patients with HF and reduced ejection fraction (HFrEF) and similar findings have been reported from other HFrEF clinical trials . Likewise, adverse outcomes associated with insulin treatment were observed in HF patients included in a large administrative registry from Italy .…”
Section: Introductionsupporting
confidence: 61%
“…Although metformin had become the most commonly used drug among patients with mild HF by 2017 (62.8%), the most commonly prescribed agent for patients with moderate‐severe HF was insulin (used in 43.1% of cases). Insulin may not appear to be the preferred agent in this population as insulin can cause fluid retention and hypoglycaemia, leading to adverse cardiovascular outcomes . However, it is possible that this observation is confounded by renal impairment, as more severe HF and higher diuretic requirement may be the cause or result of lower glomerular filtration rate, leading to prescriber hesitation regarding the use of metformin.…”
Section: Discussionmentioning
confidence: 99%
“…Antidiabetic treatment has a major effect on outcomes . Insulin may cause sodium retention and hypoglycaemia and its use has been associated with worse outcomes in patients with HF with reduced ejection fraction (HFrEF) . Shen et al .…”
Section: Co‐morbiditiesmentioning
confidence: 99%